Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Organisasi Pengelola Zakat di DKI Jakarta (Jurnal Kendali Akuntansi, 2023)
The purpose of this study was to examine whether there is an effect of the Internal Control System, the Application of the Statement of Financial Accounting Standards (PSAK) 109, Human Resource Competencies and the Use of Information Technology on the Quality of Financial Statements of Zakat Management Organisations (OPZ) in DKI Jakarta. This research method uses quantitative methods using primary data. This study uses a population of members of the DKI Jakarta zakat forum consisting of 1 BAZNAS and 7 LAZNAS with a total of 191 employees being the population with a resulting sample of 52 people. The data quality test used is validity test, reliability test. The data analysis techniques used are descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis and hypothesis testing (t test, f test and coefficient of determination test) using Statistical Package for the Social Sciences (SPSS) software. The results of this study indicate a significant joint influence of the variables of the Internal Control System, Implementation of PSAK 109, HR Competence and Utilisation of Information Technology on the Quality of OPZ Financial Statements in DKI Jakarta.